طريقة المباشرة في تدريس اللغة العربية في معهد دار السلام كونتور - Muhammad Fathan Aziz (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2017)
Arabic Language is a tool to understand the Qur'an and Hadith. This is one of the reasons that pushes Muslims to learn Arabic. Many Islamic schools are paying attention to the teaching of the Arabic language which starts from elementary school to university level. Pondok Modern Darussalam Gontor is one of the educational institutions in Indonesia that pays attention to the teaching of Arabic, therefore Gontor is known as the oldest educational institution in teaching the Arabic language since it was established in 1926. As it says in the name, Pondok Modern Darussalam Gontor is a modern Islamic educational institution, because in terms of Arabic teaching, they have been using direct method. Direct method is a method that corresponds to the nature of the language, i.e. listening to and then speaking in the language. This method relies on the student development with many exercises in listening, simulation, and communication so as to pronounce in Arabic automatically. This method shows its success in teaching Arabic in Pondok Modern Darussalam Gontor. Therefore the author wants to discuss these questions; 1) What is meant by direct method? 2) What is the effect of the direct method in Arabic teaching? 3) How is the application of direct method in teaching Arabic in Pondok Modern Darussalam Gontor?